Administrative role in supporting the Emergency Medical System in disasters - Pawłowski, Witold; Goniewicz, Krzysztof; Goniewicz, Mariusz; Czerski, Robert; Lasota, Dorota (Journal of Education, Health and Sport, 2018)
In an emergency situation, emergency services and administration Collaborating units must lead to a fast ordering in the event of disaster. They are also obligated a rapid and logical Implementation of the assistance and resources That are available and collected on in even of disaster. There is a need for the preparation of pre-developed solutions to Competent professionals, on the assessment of the risks of aid Organizations, transport and logistics tasks. The paper presents the Responsibilities of the various administration units related to the performance of tasks in the emergency medical system in the event of a disaster.